2013
DOI: 10.1002/lary.24105
|View full text |Cite
|
Sign up to set email alerts
|

Refining the role of preoperative C‐reactive protein by neutrophil/lymphocyte ratio in oral cavity squamous cell carcinoma

Abstract: The present study demonstrates that elevated CRP is an independent prognostic factor in OSCC. Elevated NLR in the high CRP group identifies patients at high risks of recurrence and shorter survival. Incorporating NLR into CRP level therefore has significant potential as a biomarker for risk stratification in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
91
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 35 publications
4
91
2
1
Order By: Relevance
“…To evaluate the relationship between inflammatory response and tumor development, researchers have recently introduced the use of inflammation-based prognostic scores, as determined by means of general serological indicators such as neutrophils, lymphocytes, CRP, and alb363738. The initial study related to the CRP/alb ratio involved a patient with a severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the relationship between inflammatory response and tumor development, researchers have recently introduced the use of inflammation-based prognostic scores, as determined by means of general serological indicators such as neutrophils, lymphocytes, CRP, and alb363738. The initial study related to the CRP/alb ratio involved a patient with a severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis demonstrated that a high LPI was an independent prognostic factor for survival. Fang et al [9] analyzed preoperative NLR and CRP levels in OSCC patients treated by ences between PI 1 and PI 2 were not significant. Median OS was 1099 days in PI 0, 500 days in PI 1, and 700 days in PI 2.…”
Section: Discussionmentioning
confidence: 99%
“…The primarily irradiated patient (non-PORT) collective was very homogenous regarding risk factors, as it consisted of predominantly locally advanced cancers (90 % stage IV cancer; 66 % T4 tumors; 79 % N2b-N3 lymph-node stage), thus, simplifying interpretation of the impact of the scoring system on OS, which was confirmed by univariate analysis (Table 7). Multivariate Cox regression analyses of the impact on OS including various factors (GPS, mGPS, PI, Primary radiotherapy or postoperative radiotherapy in patients with head and neck cancer PORT primary surgery followed by postoperative radiotherapy, GPS Glasgow Prognostic Score, mGPS modified Glasgow Prognostic Score, NLR neutrophil-lymphocyte ratio, PLR platelet-lymphocyte ratio, PI prognostic index Table 5 Inflammation-based scoring systems Type of score Score Glasgow Prognostic Score (GPS) CRP < 10 mg/l and albumin > 35 g/l 0 CRP > 10 mg/l or albumin < 35 g/l 1 CRP > 10 mg/l and albumin < 35 g/l 2 Modified Glasgow Prognostic Score (mGPS) CRP ≤ 10 mg/l and albumin ≥ 35 g/l 0 CRP ≤ 10 mg/l and albumin < 35 g/l 0 CRP > 10 mg/l 1 CRP > 10 mg/l and albumin < 35 g/l 2 Neutrophil-lymphocyte ratio (NLR) Neutrophil count:lymphocyte count < 5:1 0 Neutrophil count:lymphocyte count ≥ 5:1 1 Platelet-lymphocyte ratio (PLR) Platelet count:lymphocyte count < 150:1 0 Platelet count:lymphocyte count 150-300:1 1 Platelet count:lymphocyte count > 300: 1 2 Prognostic index (PI) CRP ≤ 10 mg/l and leukocyte count ≤ 11 × 10 9 0 CRP ≤ 10 mg/l and leukocyte count > 11 × 10 9 1 CRP > 10 mg/l and leukocyte count ≤ 11 × 10 9 1 CRP > 10 mg/l and leukocyte count > 11 × 10 9 2 CRP c-reactive protein and NLR) did not predict prognosis in the PORT group was unexpected and we are not able to provide a rationale for this observation. However, to the best of our knowledge, the relevance of prognostic scoring systems in sufficiently welldefined postoperatively irradiated treatment groups has not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophilia as an inflammatory reaction suppresses the immune system through decreasing the cytolytic activity of immune cells, for example lymphocytes, natural killer cells and activated T cells 1851 (6) . Another possible explanation is that neutrophils have been reported to secrete tumor growth promoting factors, such as circulating vascular endothelial growth factor, platelet-derived growth factor, fibroblast growth factor and matrix metalloproteinases (7) .…”
Section: Discussion:-mentioning
confidence: 99%